Morfonologia limbii romane. II. Sintagmatica. O abordare teoretica pe baza materialului verbal - Cychnerski, Tomasz (Wydawnictwo Naukowe UAM, 2003)
This paper is the second of the series of articles devoted to the morphonology of Rumanian. Its aim is to introduce the main notions of morphonological syntagmatics, such as: the morpheme’s phonological structure and its formal representation, the morpheme’s contextual achievements, their construction and conditioning. The theoretical apparatus presented here is illustrated with the examples from the Rumanian verbal inflection and word-formation.